2022
DOI: 10.1186/s12874-022-01664-z
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning approach for the prediction of 30-day mortality in patients with sepsis-associated encephalopathy

Abstract: Objective Our study aimed to identify predictors as well as develop machine learning (ML) models to predict the risk of 30-day mortality in patients with sepsis-associated encephalopathy (SAE). Materials and methods ML models were developed and validated based on a public database named Medical Information Mart for Intensive Care (MIMIC)-IV. Models were compared by the area under the curve (AUC), accuracy, sensitivity, specificity, positive and neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…However, early diagnosis and appropriate interventions can help improve the neurological prognosis of patients with SAE [13] . In previous studies focusing on machine learning risk prediction models for SAE patients, a 30-day mortality risk prediction model for SAE patients constructed by Peng et al [14] . showed that the Adapting Boosting model exhibited the best discrimination ability in the validation set, with an AUC of 0.834, and the AUC for XGBoost was 0.833.…”
Section: Discussionmentioning
confidence: 99%
“…However, early diagnosis and appropriate interventions can help improve the neurological prognosis of patients with SAE [13] . In previous studies focusing on machine learning risk prediction models for SAE patients, a 30-day mortality risk prediction model for SAE patients constructed by Peng et al [14] . showed that the Adapting Boosting model exhibited the best discrimination ability in the validation set, with an AUC of 0.834, and the AUC for XGBoost was 0.833.…”
Section: Discussionmentioning
confidence: 99%
“…It may be the reason why the mortality in our study is lower. The other study based on MIMIC-IV reported 17.62% of patients with SAE died in 30 days which was comparable with our results ( 22 ).…”
Section: Discussionsupporting
confidence: 93%
“…Their evaluation, including metrics such as AUC, accuracy, and calibration performance, adds valuable insights to the understanding of prognostic modeling in critical care settings. 23 In the context of our study, we used 10 ML models based on the MIMIC-IV database to predict in-hospital mortality risk among patients with SAE, with the stacked ensemble model emerging as the most effective.…”
Section: Discussionmentioning
confidence: 99%